Kajian Yuridis Terhadap Binary Option Trading Dalam Perdagangan Berjangka Komoditi Di Indonesia - Pranadilla, Komang Panditayana; Mochtar, Dewi Astutty; Wisnuwardhani, Diah Aju; Az, Moh. Ghufron (Bhirawa Law Journal, 2024)
Most binary options operators operate via internet-based platforms without complying with existing regulations in Indonesia. The problem discussed in this research is whether binary options are included in trading regulated in the Commodity Futures Law and legal protection for investors in binary options. This research uses normative legal research with a statutory approach. The results of this research are that Binary Options cannot meet the criteria as a commodity as regulated in Law Number 10 of 2011 concerning Amendments to Law Number 32 of 1997 concerning Commodity Futures Trading. This can be seen in the indicators listed in Article 1 number 2 of the Commodity Futures Trading Law